Associação entre desempenho motor e função cognitiva em crianças e adolescentes de 5 a 14 anos. - Guimarães, Layra Alves; de Oliveira Cunha, Cintia; Bizinotto, Thailyne; Campos, Karoline Gomes; de Souza, Gustavo Henrique Leite; Martins Roberto Formiga, Cibelle Kayenne (Motricidade, 2024)
The human development is a highly complex process that begins at birth and involves the performance of motor areas and cognitive functions. Assessing and diagnosing possible changes promotes a favourable prognosis and minimizes the consequences for motor skills. The objective of this study is to verify the association between motor performance and cognitive functions in children and adolescents aged five to fourteen years. The research is observational, transversal and quantitative. The sample consisted of 268 children and adolescents of both sexes from two municipal schools in Goiânia – GO. Data analysis was carried out at the Statistical Package for Social Sciences program for statistical analysis with the Mann-Whitney and Shapiro-Wilk U tests. The cognitive functions of the sample were assessed with the Mini Infant Mental Examination, and the broad motor skills were assessed with the Motor Competence Assessment test for the manipulative skills of the test, such as kicking and throwing. The study found that motor performance for throwing and kicking skills did not show a significant difference between cognitive performance in children and adolescents aged 5 to 14 years. Regarding differences in performance between the sexes, we found that boys had greater performance and kick speed compared to girls despite having superior cognitive performance.